EFL STUDENTS’ STRATEGIES TO IMPROVE THEIR VOCABULARIES IN CRITICAL READING CLASS - Erna Sefriani Sabuna; Lesly N. Ndun; Marthisa Oliva Billik (SAGA: Journal of English Language Teaching and Applied Linguistics, 2021)
This research attempts to find out students’ strategies to improve vocabularies size in Critical Reading class of second semester students at English Education Program of STKIP SoE. A descriptive qualitative method was used in this research. There were 21 students involved as the research participants and willing to be interviewed. The result of this research showed that students applied strategies, such as listening to the songs, watching movie, reading, and listing difficult words to improve their vocabularies. By applying those four strategies, students were able to understand vocabularies in context without any assistantship, understand the words in foreign language, repeat the words several times, describe the conversation in mother tongue, pick some words when reading books, remember the words that they get, and write down some difficult words.